Plasma exchange in hypertriglyceridaemic acute pancreatitis: case report - Cunha,Cátia (2016)
Severe hypertriglyceridaemia, defined as above 1000mg/dl, is the third most common cause of acute pancreatitis, and a potentially life-threatening condition. The prognosis depends greatly on our ability to rapidly reduce serum triglycerides concentration. We report a case of a 41-year-old male admitted to our Emergency Department with symptoms of nausea, vomiting and abdominal pain in the right upper quadrant, whose workup revealed the presence of an extremely severe hypertriglyceridaemia (triglycerides 16422 mg/dl), and acute oedematous non-lithiasic pancreatitis. Plasma exchange was initiated at admission and reduced triglycerides concentration to less than half. Two additional sessions of plasma exchange in the subsequent days, associated with pharmacological treatment of hypertriglyceridaemia, achieved a normal triglycerides level at discharge and allowed a favourable clinical evolution with rapid resolution of the pancreatitis